AN ANALYTICAL STUDY OF THE BODILY-KINETIC INTELLIGENCE OF EXCELLENT CLASS HANDBALL PLAYERS - Asst. Lect. Saad Khudhair Najd; Prof. Dr Hayder Odda Zeghair (Scholars Digest Publishing, 2024)
Intelligence is of great importance and is evident in all areas of life, including the sports field. Like other societies and institutions, the right individual is placed in the right place. This requires identifying the mental potential of the handball player in accordance with the requirements of the role played by the handball player. The nature of handball requires a leader who has With several qualities, including physical, psychological, scientific, and educational, in addition to the physical and motor intelligence that he is required to have in his work, especially when staying with a hero, and whose ability is likely to do what is best for his group, which is the test of their superiority, and the matter is not limited to cognitive capabilities, but goes beyond that to include non-cognitive capabilities, represented by With skills that have a major role in the success of work This is what makes us find intelligence, which is considered mental energy or mental return, or is the characteristic that accompanies the mind that works with the activity, understanding, depth, and speed of a leader’s behavior. To the researchers’ knowledge, there is no measure of field intelligence in the sports field. The researchers hope, through this study, to reach results that have positive implications for... Different aspects in the sports field The research aimed to build and apply a measure of bodily-motor intelligence among excellent class handball players Finding standards and levels of field intelligence and identifying it among handball players, excellent class. Building and applying a measure of bodily-motor intelligence among handball players, excellent class. Finding standards and levels of field intelligence and identifying it among soccer players Handball Premier Division included a number of club players participating in the Premier Division Handball League, numbering (176) players, representing (73.33%) of the research community. The most important conclusions were that the player who has a high level of bodily-kinetic intelligence is reflected in his performance in matches and training and is more positive, unlike the player who has a low level of bodily-kinetic intelligence.
Keywords: Intelligence: Bodily-kinesthetic intelligence: standards and levels for field intelligence.